Kolaborasi Aktor Pentahelix pada Rekrutmen Tenaga Kerja Berbasis Arek Suroboyo Siap Kerjo - Tiboyong, Wilna Gebilya; Hertati, Diana (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This study aims to determine and describe the collaboration of pentahelix actors in Arek Suroboyo Siap Kerjo-based recruitment. The research method uses a qualitative descriptive approach. In collecting data, collection techniques are carried out through observation (observation), interviews, and documentation as secondary sources. The results showed that the collaboration was quite good. In terms of actor selection, it has fulfilled the aspects of the pentahelix element, which consists of academics, business, government, community and media. In terms of roles, each actor has carried out his role well to support the success of the Arek Suroboyo Siap Kerjo program. In terms of communication and coordination, it shows results that have not been maximized, because communication and coordination are conditional and have not involved pentahelix actors as a whole. However, when referring to the target of labor placement, it has given good results. This can be seen from the target of labor placement exceeding 50% of the number of job seekers registered on the Arek Suroboyo Siap Kerjo application.